Resistance to the implementation of learning management systems by lecturers in higher education in a developing country context - Sakala, Lucy Charity (Department of Information Systems, 2019)
Problem Statement: The implementation and use of Information Communication Technologies (ICTs) has been ascribed as a transformative drive across the world, especially to improve the human capacity development of individuals in Higher Educational Institutions (HEIs). However, developing countries are still struggling to harness the productive capacity of their ICT resources. The ICT index of ‘access, use and skills’ in developing countries is less than 50%, whilst that for developed countries is above 75%. Whilst HEIs have incorporated ICTs, the uptake of the Learning Management Systems (LMS) is low, with the expected objectives remaining largely unachieved and the full potential of the technologies not realised. A myriad of challenges have contributed to the low uptake of ICT projects in resource-limited settings ranging from limited ICT expertise, cost and complexity of implementation, inadequate training, lack of top management support, poor organisational culture, limited infrastructure and resistance to change. Whilst these challenges play a significant role in limiting uptake, the role of user resistance to LMS implementation in HEIs has not been fully explored. Purpose of study: This study offered an explanatory critique of user resistance and its implications on low uptake of LMS in HEIs. The objective was to examine how resistance behaviours manifested from lecturers during implementation of an LMS in an HEI of a developing country context. The study identified different forms of lecturer resistance behaviours and examined how they manifested to cause low uptake of the LMS. It also analysed the nature of responses and/or strategies from management and ICT implementers towards the lecturer resistance behaviours during LMS implementation. Furthermore, the study examined how contextual factors influenced manifestation of resistance practices in relation to habitus, capital and field positions of lecturers, management and ICT implementers. Research methodology: The study adopted an interpretive research paradigm and drew on Bourdieu`s Theory of Practice (TOP) framework and the Multilevel Model of Resistance to Information Technology Implementation (MRITI) as theoretical lens, to analyse the manifestation, interaction and logic of user resistance towards LMS implementation in HEIs. The study analysed data from semi-structured interviews and project documents to highlight issues of incorporating ICTs into teaching and learning. More data and field notes came from participant observations during the implementation of the LMS (Moodle). The case of Omega University in Zimbabwe was used as a representation of an HEI in a developing country context. Key findings: User resistance affected the implementation and uptake of Moodle. The different forms of resistance behaviours that manifested from lecturers during Moodle implementation were disinterest, minimal use, refusal to use, pessimism, withdrawal, avoidance, prioritisation and delegation. The forms were classified into four episodes; apathy, passive resistance, covert resistance and active resistance. Aggressive forms of resistance were not found in this study. Delegation of responsibilities was a unique form in that it falsified and misrepresented acceptance of Moodle despite harbouring resistance tendencies; like two sides of the same coin. Resistance behaviours manifested during Moodle implementation due to initial conditions that interacted with objects and triggers of resistance to generate perceived threats in lecturers. Initial conditions were Omega`s management model, its ICT structure and ICT culture, whilst the objects of lecturer`s resistance were mostly towards ‘Moodle advocates’ and less towards ‘Moodle features’ or ‘Moodle significance’. Therefore, lecturer resistance behaviours were directed towards external rather than internal factors with regard to the LMS. The triggers of lecturer resistance were grouped into management, infrastructure and personal triggers. Perceived threats from lecturers were either fear of loss of relevance, status, jobs or increased workloads. The positive responses and/or strategies from management and ICT implementers were acknowledgment, reward innovation, rectification, effective training and user consultations, whilst the negative responses were inaction, dissuasion, enforcement, no reward for innovation, ineffective training, and absence of change management. Due to other underlying contextual factors, the nature of these responses neither reduced lecturer resistance nor enhanced the low uptake of Moodle. Contextual factors in form of differences in habitus and forms of capital influenced lecturer resistance as well as practices of management and ICT implementers during Moodle implementation. Lecturer resistance was caused by the following habitus: prior exposure to technology, age-related habitus, technophobia and pedagogical beliefs and the following forms of capital: qualifications, position, academic titles and employment status. The practices of management and ICT implementers were driven by the habitus of implementing, supporting, training of ICT projects, providing ICT infrastructure as well as developing and enforcing ICT policies. The following forms of capital motivated management and ICT implementers` practices: prestige, honour, level of Moodle expertise and university positions. Contribution of the study: The study contributed to knowledge, theory and practice. First, the study provided a deeper conceptualisation of user resistance towards the implementation of ICT projects and suggested theoretical propositions to explain how lecturer resistance manifested during the implementation of LMS in HEIs. Second, the study developed a unified conceptual framework by integrating Bourdieu`s TOP and MRITI to explain resistance practices during LMS implementation in HEIs. Third, the study provided recommendations for managers and ICT implementers in Zimbabwean HEIs and similar contextual settings, to address user resistance issues by creating effective responses and strategies aimed at improving the design, implementation and uptake of LMS in HEIs. Additionally, recommendations were provided for HEIs who wish to achieve ‘technological determinism’ and/or ‘techno-centrism’, to implement policies that equip intended technology users with all the knowledge components of TPACK (Technology, Pedagogy and Content Knowledge). Finally, technology implementers should resolve exogenous issues in the institution before system implementation to avoid users directing focus on endogenous factors. This intervention and understanding may lead to the realisation of the full potential of ICT projects and achievement of expected objectives in HEIs of developing countries.